Assessment of performance of services in a tertiary care Neuropsychiatric Institute using Pabon Lasso Model - Tripathi, Chandra Bhushan; Kumar, Rajesh; Sharma, Ramesh Chandra; Agarwal, Rachna (Asian Journal of Medical Sciences, 2016)
Background: The objective of the study to assess optimal utilisation of hospital facilities & evaluate their performance in a tertiary care hospital using Pabon Lasso Model using indicators- bed turnover (BTO), bed occupancy rate (BOR) and average length of stay (ALS). Aims and Objective: To assess optimal utilisation of hospital facilities various wards catering to psychiatric, neurological and neurosurgery services in a tertiary care hospital using Pabon Lasso model and to identify strategies for more efficient use of the existing health service resources. Materials and Methods: This cross-sectional descriptive study was carried out in 2015 at the Institute of Human Behaviour and Allied Sciences, Delhi, India. This study involved various wards catering to psychiatric, neurological and neurosurgery facilities in the institute. Their performance was evaluated over 8 year period (2007- 2014) using three performance indicators (BTO, BOR & ALS) to assess optimal utilisation of hospital facilities. Results: Psychiatry department was initially located in quadrant IV in 2007 & shifted to quadrant III in 2014 which suggests department’s good quantitative performance with small proportion of unused beds. Similarly Neurosurgery department was in quadrant I at its inception in 2010, but shifted to quadrant III in 2014. However, Neurology department was located in quadrant III initially (2007), but shifted to quadrant II indicating either excess bed supply or less need for utilisation. Conclusion: Pabon Lasso model can be used by hospital management for evaluating the performance of health services in cost effective manner. Asian Journal of Medical Sciences Vol.7(5) 2016 69-74